2020
DOI: 10.31014/aior.1992.03.01.200
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Stock Returns of Nigerian Quoted Firms: A Two-Sector Comparative Analysis

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Their study revealed distinct differences in how firm characteristics influence stock returns across sectors, with earnings per share, liquidity, and market capitalization playing significant roles. This comparative analysis sheds light on the sectorspecific factors that manufacturing companies must consider when implementing financial modeling techniques to enhance their market performance and operational efficiency (Peter, Ojo, & Adewoye, 2020). The synthesis of these studies illustrates the multifaceted nature of implementing advanced financial modeling techniques in inventory management across different manufacturing contexts.…”
Section: Effectiveness Of Various Strategies In Different Manufacturi...mentioning
confidence: 95%
“…Their study revealed distinct differences in how firm characteristics influence stock returns across sectors, with earnings per share, liquidity, and market capitalization playing significant roles. This comparative analysis sheds light on the sectorspecific factors that manufacturing companies must consider when implementing financial modeling techniques to enhance their market performance and operational efficiency (Peter, Ojo, & Adewoye, 2020). The synthesis of these studies illustrates the multifaceted nature of implementing advanced financial modeling techniques in inventory management across different manufacturing contexts.…”
Section: Effectiveness Of Various Strategies In Different Manufacturi...mentioning
confidence: 95%